Coach perspectives on coach-athlete relationships and characteristics of Generation Z academy level rugby union players from South Africa - Landman, Marc; Grobbelaar, Heinrich; Kraak, Wilbur (Frontiers in Sports and Active Living, 2024)
Introduction: The coach-athlete relationship is not merely a by-product of the coaching process but serves as its foundation. Coaches today must align their approaches with the characteristics (character, strengths, and growth areas) of a new generation of athletes, commonly referred to as Generation Z (Gen Z). Born between 1995 and 2012, Gen Z's grew up in a digital age, which shaped their character and behaviour. The purpose of the study was to explore coach-athlete relationships, the characteristics of Gen Z athletes that influence this relationship, and the process of building healthy coach-athlete relationships, from the perspectives of coaches. Methods: The study used a qualitative methodology to elicit the perspectives of 11 male rugby union coaches (M ± SD age: 42.09 ± 7.56 years; with 12.83 ± 3.48 years of coaching experience), through semi-structured individual online interviews. We developed the interview script from Jowett's Coach-Athlete Relationship Questionnaire (CART-Q). The interviews were analysed using Merriam and Tisdell's six-step process. Findings: and The analysis yielded six super themes (and 17 themes). 1. Coach perspectives on coaching Gen Z players (developmental facilitators and debilitators, Covid-19's effect on development). 2. Closeness between coaches and athletes (loving and caring, getting closer, trusting, (not) respecting some players). 3. Commitment (personally and towards the team, sacrifices). 4. Complementarity (goal setting, collectively working towards common goals). 5. Co-orientation (communicating, reciprocal relationship views). 6. Developing the coach-athlete relationship (approaches thereto, practical steps). Discussion: Various facets of the coach-athlete relationship are interlinked and shaped by the characteristics and behaviours of this generation of athletes. Practical recommendations are offered on how to cultivate the coach-athlete relationship on emotional, cognitive, and behavioural levels.